Comparison of simulations on the NewMexico rotor operating in pitch fault conditions. Issue 2 (September 2016) - Oggiano, L; Boorsma, K; Schepers, G; Kloosterman, M
Abstract: The present paper aims to simulate and reproduce the experiments on a imbalanced rotor with one blade off pitched by 20degees carried out within the IEA task 29 Mexnext Phase III. Models of increasing complexity were used (Blade Element Method simulation (BEM) lifting line with free vortex wake (FVW) and URANS CFD) and the results were compared. The rotor has a diameter of 4.5m and three different load cases corresponding to a tip speed ratio of 5.24, 7.6 and11.2 were chosen from the test matrix performed during the experiments. The rotor speed was kept constant at 324.9RPM. BEM and FVW simulations were performed using the Aero Module tool developed by ECN that offers both an advanced BEM formulation and a FVW formulation named AWSM. The commercial solver STARCCM+ was for the CFD simulations and an Unsteady RANS approach with the k-ra SST turbulence model was chosen. Loads recorded with strain gauges during the experiments and pressures on the equipped blades were compared with results from the numerical simulations. The comparison provided good agreement in the low tip speed ratio cases while differences were more noticeable for the highest tip speed ration load case.